Consequences for conservation: population density and genetic effects on reproduction of an endangered lagomorph. Issue 3 (26th April 2016) - DeMay, Stephanie M.; Becker, Penny A.; Waits, Lisette P.; Johnson, Timothy R.; Rachlow, Janet L.
Abstract: Understanding reproduction and mating systems is important for managers tasked with conserving vulnerable species. Genetic tools allow biologists to investigate reproduction and mating systems with high resolution and are particularly useful for species that are otherwise difficult to study in their natural environments. We conducted parentage analyses using 19 nuclear DNA microsatellite loci to assess the influence of population density, genetic diversity, and ancestry on reproduction, and to examine the mating system of pygmy rabbits ( Brachylagus idahoensis ) bred in large naturalized enclosures for the reintroduction and recovery of the endangered distinct population in central Washington, USA. Reproductive output for females and males decreased as population density and individual homozygosity increased. We identified an interaction indicating that male reproductive output decreased as genetic diversity declined at high population densities, but there was no effect at low densities. Males with high amounts (>50%) of Washington ancestry had higher reproductive output than the other ancestry groups, while reproductive output was decreased for males with high northern Utah/Wyoming ancestry and females with high Oregon/Nevada ancestry. Females and males bred with an average of 3.8 and 3.6 mates per year, respectively, and we found no evidence of positive or negative assortative mating with regards to ancestry. Multiple paternity was confirmed in 81% of litters, and we report the first documented cases of juvenile breeding by pygmy rabbits. This study demonstrates how variation in population density, genetic diversity, and ancestry impact fitness for an endangered species being bred for conservation. Our results advance understanding of basic life history characteristics for a cryptic species that is difficult to study in the wild and provide lessons for managing populations of vulnerable species in captive and free‐ranging populations.